Influence of different types of non-resorbable suture material on the healing of extraction wounds--a histological study in rats. - Okamoto, T.; Gabrielli, M. F.; Gabrielli, M. A. (Nihon University School of Dentistry, 1990)
The influence of different non-resorbable suture materials on the healing of tooth extraction wounds was examined in 120 adult male albino rats. Nylon gave the best biological results for healing of the mucosa and dental socket. Silk and cotton produced considerable delay of socket healing. Healing was only mildly delayed by polyester suture, with a short moderate inflammatory reaction at the initial stage.
Keywords: nylon; polyester; protein; animal; connective tissue; epithelium; gingiva; gossypium; histology; jaw; male; rat; rat strain; silk; suture; time; tooth extraction; wound healing; Alveolar Process; Animal; Connective Tissue; Epithelium; Gingiva; Gossypium; Male; Nylons; Polyesters; Proteins; Rats; Rats, Inbred Strains; Sutures; Time Factors; Tooth Extraction; Wound Healing